Selenium and breast cancer risk: A prospective nested case–control study on serum selenium levels, smoking habits and overweight. Issue 9 (19th July 2017) - Sandsveden, Malte; Manjer, Jonas
Abstract : Previous research has not been conclusive regarding the association between selenium (Se) and breast cancer. This study was conducted to clarify if there is an association between prediagnostic serum Se levels and breast cancer risk. A population based cohort, the Malmö Diet and Cancer Study, was used and linked with the Swedish cancer registry up to 31 December 2013. Our study included 1, 186 women with breast cancer and an equal number of controls. Selenium levels were analysed from stored serum samples. The included individuals were divided into quartiles based on Se value and we compared breast cancer cases with controls using logistic regression yielding odds ratios (OR) with 95% confidence intervals. Serum Se was also analysed as a continuous variable regarding breast cancer risk. The analyses were adjusted for established risk factors and stratified on smoking status and body mass index (BMI). When comparing the highest Se quartile with the lowest, the adjusted OR for breast cancer was 0.98 (0.75–1.26). With selenium as a continuous variable the adjusted OR was 1.00 (1.00–1.01) per 10 ng/ml. When comparing the highest with the lowest Se quartile in women with BMI > 25 kg/m 2 the adjusted OR was 0.77 (0.53–1.14). We conclude that it is unlikely that prediagnostic serum selenium is overall associated with breast cancer risk and no modifying effect from BMI or smoking was seen. Abstract : What's new? Selenium, a micronutrient integrated in several proteins with anti‐oxidative and possibly transcription and cell proliferation regulatory functions, has been suggested to be protective against breast cancer. The evidence, however, remains inconclusive. Here, the authors set to clarify if there is an association between pre‐diagnostic serum selenium levels and breast cancer risk by studying 1, 186 cases, making this study larger than all the previous prospective studies combined. The analyses were adjusted for established risk factors and stratified on smoking status and body mass index. The results do not support an overall association between prediagnostic serum selenium and breast cancer risk.